Analysis of the Diversity of Student Backgrounds in Learning and the Urgency of Multicultural Education - Roby Salim; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study focuses on the discussion of the diversity of student backgrounds in learning, especially on cultural influences, socioeconomic status, ethnicity / race, gender, language differences, and also multicultural dimensions. This study aims to determine the various influences contained in the classroom and how students adapt to a multicultural environment. This research uses qualitative methods. The results of this study show the influence resulting from cultural differences, differences in socioeconomic status, racial differences, ethnic differences, gender differences (sex), language differences. And also the concept of the dimensions of multicultural education.